Anthrax, among the living celebrating 40 yearsof Anthrax - Zombie, Rob 1966-; Posehn, Brian 1966-; Azzarello, Brian 1962- (Z2 Comics, 2021)
In 1987, Anthrax unleashed a heavy metal & pop culture touchstone with the release of their historic Among the Living album! Now Anthrax & Z2 invite you to explore the album like never before with this original anthology graphic novel! Each song on the album is given an original story by an amazing creative team, along with extra content and the introduction of the new NOTMAN designed by Greg Nicetero (Walking Dead)! Come on this dark journey into the '87 underground in America with these esteemed creators...
Keywords: Anthrax -- Musikgruppe; Ungeheuer; Comic